Methodik der Rechtsfindung - insbesondere im japanischen Strafrecht - Ida, Makoto (Zeitschrift für Japanisches Recht, 2009)
In this article, the author presents an overview of several aspects concerning the interpretation of statutes in Japan. The author exemplifies his analysis with decisions by the Supreme Court and points out differences to the German law and jurisdiction. One significant aspect is the importance of the wording of the law, which in Japan is dealt with in a more flexible way regarding the range of possible interpretations and the principle of certainty. Another element, the principle of “historical interpretation” of statutes, is of limited importance where − as in the case of the Japanese Criminal Code − it is difficult to detect the aims pursued by the original lawmakers. Furthermore, the article outlines the postwar development of the discourse on legal positivism, value judgments and their possible objectification by empirical and systematic approaches. The author demonstrates that Japanese law is characterized by casuistic interpretations of the statutes. As an example he gives the theory of adequate causation, which has been rejected by the Supreme Court in favor of a case-by-case interpretation in each judgment. Another example of the increasing flexibility and the renunciation of a systematic approach is the Organ Transplantation Law of 1997. It provides that a potential organ donor is to decide himself, by using a donor card, whether the time of death should be defined by brain death or cardiac arrest. The author concludes that only legal discourse itself can help to overcome the uncertainties which remain with regard to statutory interpretation. (The editors)